Effects of a mobility monitoring system on the cost of care in relation to reimbursement at Swiss nursing homes: Learnings from a randomized controlled trial - Mario Stark; Rigo Tietz; Heidrun Gattinger; Virpi Hantikainen; Stefan Ott (Health Economics Review, 2017)
Background/objective: Nursing homes in Switzerland are under pressure to efficiently coordinate staff activities to cover their personnel costs under the care financing system. In this study, the use of a mobility monitoring system accompanied with case conferences was investigated in order to improve sleep quality and estimate the cost benefit of this intervention. Method: In an open two-phase randomized controlled trial at three nursing homes, residents with cognitive impairment were randomly assigned to an intervention group and a control group. In the intervention group, a 10-week period of intensive use of the monitoring system and case conferences led by an advanced nurse practitioner (Phase I) was followed by 3 months of reduced use of the monitoring system and case conferences led by an internal registered nurse (Phase II). In the control group, the monitoring system was only used for data acquisition. Nurses reported the activities with a specifically developed tool. Based on the recorded activities, the cost of care was calculated. The correlating reimbursement per patient was calculated from the care levels in the Swiss reimbursement system. Data from 44 residents was included in the analysis with a linear mixed model. Results: Although analysis revealed no statistically significant effects, results indicate that the use of a monitoring system can guide nurses in organizing their tasks to increase effectiveness. Information systems such as the mobility monitor can help to identify single outliers that do not correspond with the overall situation. Conclusion: In the health care system, problematic individual cases can account for a disproportionally high cost levels. It was shown that information systems can have a significant economic impact in the long run. Trial registration: The study is registered at the German Clinical Trials Register under the Nr. DRKS-ID: DRKS00006829.
Keywords: 330; Health economics; Cost of care; Reimbursement; Monitoring system; Nursing home